Occupational stress-induced consequences to employees in the context of teleworking from home: A preliminary study - Agota Giedré Raišiené; Evelina Danauskė; Karolina Kavaliauskienė; Vida Gudžinskienė (Administrative Sciences, 2023)
Challenges when many people moved their jobs from the office to home because of COVID-19 pandemic restrictions have put stress on employees' daily routine and professional lives. This article investigated the experience of individuals working not at the office and disclosed consequences of occupational stress such as mental and physical exhaustion, social deprivation, decreased work commitment, professional cynicism, and professional burnout. The preliminary study was based on a survey of 202 employees in Lithuania who were teleworking from home throughout the pandemic. According to the results, it can be assumed that teleworking had rather negative effects on employee wellbeing, as many teleworkers tended to suffer mental and physical exhaustion and social deprivation when working from home within pandemic. The psycho-emotional state of employees seems to be a key factor influencing the intellectual resources of an organization in a period of uncertainty.
Keywords: 350; burnout; Lithuania; occupational stress; work commitment; work-from-home